Mean-Variance Portfolio Optimisation Model for Comparison of Stock Portfolio Composition on the American Stock Exchange before and after the Boycott of Companies Supporting Israel (Case Study: AAPL, SBUX, AMZN, GOOGL, MCD) - Fasa, Rayyan Al Muddatstsir; Sukono, Sukono; Salih, Yasir (International Journal of Quantitative Research and Modeling, 2024)
The background of this research is related to the boycott of companies that support Israel, which affects the composition of stock portfolios on the American Stock Exchange. The focus of this research is on key companies such as Apple (AAPL), Starbucks (SBUX), Amazon (AMZN), Google (GOOGL), and McDonald's (MCD). The problem to be solved is the identification of changes in optimal asset allocation in investment portfolios before and after the boycott. Using a mean-variance portfolio optimization model, historical stock price data is analyzed to model the transformation of portfolio composition as well as the associated risk level. The purpose of this study is to provide an in-depth understanding of the impact of the boycott on the investment portfolio structure of related companies on the American Stock Exchange. The result of this research is that there is a change in the allocation of assets held against stocks before the boycott and after the boycott. This research is expected to provide useful insights for investors, financial analysts, and other stakeholders in managing their investment portfolios, especially in anticipating and adjusting investment strategies amid dynamic changes in the stock market.